Effects of polyglycerol esters on palm olein fractionation - Yoong, Jun Hao (2017)
Palm olein fractionation is an important process to produce palm super olein which has iodine value higher than 56 for market access to temperate countries. The process is, however, energy consuming and costly due to its lengthy cooling time in crystallization. Polyglycerol esters are introduced in the palm olein fractionation to enhance the process by reducing the crystallization time. This study investigated the effects of 0.1% (w/w) – 0.9% (w/w) polyglycerol esters on palm olein fractionation from the aspects of crystal nucleation, crystal growth and product quality. Palm olein (iodine value 56) with 0.1% (w/w), 0.3% (w/w), 0.5% (w/w), 0.7% (w/w) and 0.9% (w/w) polyglycerol esters additives were cooled to its desired crystallization temperature at 13ºC in 335 minutes using the focused beam reflectance measurement. Crystal nucleation and growth during the crystallization were monitored in the focused beam reflectance measurement where the in-line changes of crystal size distribution during the crystallization were analysed. The product quality of the palm olein fractionation was analysed using iodine value test and triacylglycerol composition. Our research findings from focused beam reflectance measurement showed that polyglycerol esters promote crystal nucleation and less formation of undesired large crystals were observed during the palm olein crystallization. Polyglycerol esters expedited the crystal nucleation as compared with the control without polyglycerol esters. The product analysis found that polyglycerol esters prevent olein entrainment in the solid fraction after filtration where the content of 1,3- dipalmitoyl-2-oleyl-glyerol in the solid fraction increased while its 1-palmitoyl-2,3- oleyl-glycerol content decreased. The optimal dosage that offered best performance was 0.3% (w/w) polyglycerol esters which gave formation of the most medium crystals and best palm mid fraction product with lowest iodine value and highest content of 1,3- dipalmitoyl-2-oleyl-glycerol. These results imply that polyglycerol esters are a nucleation enhancing and crystal growth retarding additive in palm olein crystallization at 0.3% (w/w) dosage.